(untitled) (International Journal of Statistical Sciences, 2026)
Students’ problem-solving ability (PSA) is important in both school and daily life, making it essential to understand and identify the factors that influence its development. This study aims to examine the prevalence and determinants of PSA among secondary and higher secondary students in Muslim societies. This study used data from the Advancing Education in Muslim Societies: Mapping the Terrain 2019-2020 project. The PSA status was treated as the response variable, while socio-demographic factors were analyzed as predictors. To achieve the study’s objectives, both bivariate and multivariate statistical methods were utilized to analyze the data. The bivariate analysis revealed a significant relationship between PSA and various socio-demographic factors, including religion, type of school, academic grades, and country of residence. Notably, Muslim students demonstrated higher PSA than Christian and Buddhist students but lower than Hindu students. Students attending private schools showed the higher PSA compared to their public-school counterparts. Furthermore, PSA tended to decline with increasing age and higher grade levels. Socio-demographic factors significantly influenced students’ PSA in the Muslim Societies Mapping Terrain. The study recommends introducing an age-based, problem-oriented learning approach to enhance PSA, especially for private school and Muslim students. These findings can guide the development of comprehensive programs to improve PSA among students in Muslim societies. IJSS, Vol. 26(1), March, 2026, pp 83-94